ChemInform Abstract: 6‐Alkynyl‐ and 6‐Aryl‐Substituted (R)‐Pipecolic Acid Derivatives. Issue 40 (12th September 2013) - Sadiq, Amina; Sewald, Norbert
Abstract Compound I is derived from (R)‐α‐aminoadipic acid.